2011
DOI: 10.3810/psm.2011.02.1854
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Training for Children and Adolescents: Techniques and Practices for Reducing Sports-Related Injuries and Enhancing Athletic Performance

Abstract: As more children and adolescents participate in sports and conditioning activities (sometimes without consideration for cumulative workload), it is important to establish age-appropriate training guidelines that may reduce the risk of sports-related injury and enhance athletic performance. The purpose of this article is to review the scientific evidence on youth strength and conditioning and to provide age-appropriate recommendations for integrating different strength and conditioning activities into a well-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 86 publications
(116 reference statements)
1
114
0
3
Order By: Relevance
“…[19][20][21][22] Whereas only a small number of young athletes participate in preparatory conditioning programs before sports involvement, 23 current data have indicated that multifaceted interventions may reduce sport-related injury risk in adolescents, and we hypothesize that similar results will be observed in preadolescent populations if such programs are applied before the development of fundamental movement deficits. 21,22,[24][25][26][27] Given that research on the specific effects of INT during childhood is scant, investigators need to determine if a brief sex-specific time of development exists for implementing INT so that certified athletic trainers and other professionals can optimize training adaptations during the growing years in both boys and girls.…”
mentioning
confidence: 74%
“…[19][20][21][22] Whereas only a small number of young athletes participate in preparatory conditioning programs before sports involvement, 23 current data have indicated that multifaceted interventions may reduce sport-related injury risk in adolescents, and we hypothesize that similar results will be observed in preadolescent populations if such programs are applied before the development of fundamental movement deficits. 21,22,[24][25][26][27] Given that research on the specific effects of INT during childhood is scant, investigators need to determine if a brief sex-specific time of development exists for implementing INT so that certified athletic trainers and other professionals can optimize training adaptations during the growing years in both boys and girls.…”
mentioning
confidence: 74%
“…As such, it seems that the musculoskeletal system of some aspiring young athletes may be ill-prepared for the demands of sports practice and competition 25 29 138 139. Recent position statements have recognised the importance of physical activity and sport for youth, and promote the early identification of fitness deficits in aspiring young athletes and the proper prescription of training programmes to address individual limitations 140 141.…”
Section: Injury Prevention Benefits Of Resistance Training For Youthmentioning
confidence: 99%
“…From a health perspective, evidence indicates that resistance training can make positive alterations in overall body composition,18 reduce body fat,19 20 improve insulin-sensitivity in adolescents who are overweight21 and enhance cardiac function in children who are obese 22. Importantly, it has also been demonstrated that regular participation in an appropriately designed exercise programme inclusive of resistance training, can enhance bone-mineral density and improve skeletal health23 24 and likely reduce sports-related injury risk in young athletes 25 26. This would appear to be an important consideration given that approximately 3.5 million sports-related injuries in youth require a medical visit each year in the USA 27.…”
Section: Introductionmentioning
confidence: 99%
“…Programs must ensure that improvements in physical ability are made on top of a strong fundamental movement capacity (17,(23)(24)(25). Strength training gains illustrated in the meta-analysis of resistance training effects in adolescents show a relationship between longer programmed interventions and programs involving more sessions per week, although in female athletes the effect size (ES) of this increase is still unclear particularly after the initial increase in performance due to neural adaptation (9).…”
Section: Introductionmentioning
confidence: 97%